Acute and chronic cholinergic activity in the inflammatory and lipid regulation of epicardial stromal cells from patients with and without atrial fibrillation. (25th November 2020) - Couselo Seijas, M; Fu, X; Lopez-Cano, J.N; Rozados-Luis, A; Fernandez, A.L; Seoane, L.M; Duran-Munoz, D; Gonzalez-Melchor, L; Rodriguez-Manero, M; Gonzalez-Juanatey, J.R; Eiras, S
Abstract: Aims: Acetylcholine (ACh) released modulation by botulinum toxin injection into epicardial fat diminish atrial fibrillation (AF) recurrence. These results suggest an interaction between autonomic imbalance and epicardial fat as risk factors of AF. Our aim was to study the inflammatory and lipid profile of epicardial stroma from AF patients and their regulation by high cholinergic activity. Methods and results: We performed in vitro assays with primary cultures from paired subcutaneous and epicardial stromal cells from 33 patients. We analysed ACh effect on gene expression, intracellular calcium mobilization and neutrophil migration. Plasma protein regulation by parasympathetic denervation was performed in vagotomised rats. Acute ACh treatment up-regulated MCP1 levels on epicardial stromal cells and suggested a neutrophil infiltration enhancement. Patients with AF had a greater FABP4 gene expression (1.54±0.01 vs 1.47±0.01, p=0.005). Its plasma levels were pronouncedly declined on vagotomised rats (2.02±0.21 ng/mL vs 0.65±0.23 ng/mL, p<0.001). Additionally, chronic ACh treatment improved lipid accumulation within epicardial stromal cells (60.50% [22.82–85.13] vs 13.85% [6.17–23.16], p<0.001). Conclusions: Acute ACh activity up-regulates MCP1 and calcium mobilization on epicardial stromal cells. Longer ACh treatment enhanced lipid accumulation. In this line, epicardial stroma from patients with permanent AF contains higher FABP4 expression levels. Thus, modulate cholinergic activity might reduce FABP4 since vagus nerve denervation is associated with a sharply decrease in FABP4 plasma levels. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Carlos III Health Institute; Health Research Institute of Santiago de Compostela